Does Resilience Help in Reducing Burnout Symptoms Among Chinese Students? A Meta-Analysis - Gong, Zhun; Li, Chunqin; Jiao, Xinian; Qu, Qunzhen (Frontiers in Psychology, 2021)
As society has evolved, student burnout has become a common problem in schools around the world, including in China. Therefore, the purpose of the current study is to explore whether resilience is related to student burnout in China and to examine the changing trend of resilience and student burnout. Moreover, we will assess gender differences and possible biases, including publication biases, small-study biases, grey literature biases, and decline effects. This meta-analysis included 34 studies, with a total of 81 effect sizes and a total sample size of 22,474. We found that resilience was negatively correlated with student burnout in the Chinese context. We found evidence of grey literature bias in student burnout, which needs to be verified by subsequent studies. However, we found that there were decline effects in resilience, possibly because as culture evolves, people become more focused on themselves, and collective behaviours are declining, leading to a decrease in their ability to adapt to the collective and the environment. We also found similar decline effects at the individual level; that is, resilience might decrease with individual age stages (from the primary to college stage), which might be related to the use of immature defence mechanisms against stress by students.